Improved Vacuum Dewatering of Grease-proof Paper Utilizing a Multi-slit Vacuum Suction Box in Laboratory Scale - Björn Öman; Björn Sjöstrand (BioResources, 2024)
Grease-proof paper is an energy-demanding paper product to manufacture, especially during refining and dewatering. Increases in energy efficiency in either stage could result in major savings. This article investigates the potential gains with addition of a stepwise progression vacuum suction box to the forming section during production. For both a lighter, 50 g/m2, and a heavier paper grade, 100 g/m2, with a pulp-drainability of 86 °SR, a stepwise progression vacuum suction box in four steps would result in increased dryness, simultaneously with decreased energy expenditure. The observed effects were higher for the lower basis weight paper (50 g/m2). Both basis weights experienced clogging of the forming fabric due to the high degree of refining. This adversely affected the dewatering rate, decreasing the amount of air pulled through the paper even when increasing the vacuum pressure. When a stepwise progression suction box in four steps was compared to a single vacuum suction box, there was a 14% increase in dryness for lighter paper, over an equal energy consumption, measured as amount of air pulled through the paper. For the 100 g/m2 paper, the increase in dryness was 3% compared to the 50 g/m2 paper run over a single vacuum suction box. The results show great promise for energy savings when utilizing stepwise progression suction box dewatering for grease-proof paper production.